Selfish, Scared and Stupid - Gregory, Dan (Ascent Audio, 2017)
IF YOU WANT TO SUCCEED ... PREPARE FOR FAILURE! Why is change so difficult? Why are leaders experiencing unprecedented levels of disengagement? Why are sales people falling so short of their targets? And, perhaps most importantly, why is it that so many seemingly sound businesses and worthy causes falter, relegating exciting new ideas to the scrap heap? After years of having motivational smoke blown up our collective backsides we've started to act as if we are all generous, bold and intelligent-all of the time! We've designed our organizations, teams, systems, products, relationships and lives so we can only succeed under ideal 'laboratory' conditions. Anything less than perfection often means catastrophe. The problem is that's not how human beings work at all. Behavioral strategists Dan Gregory and Kieran Flanagan argue that if you want to increase your chances of success in business and life, you should design for reality. Offering real-world strategies with a healthy dose of wit and charm, Selfish, Scared & Stupid will help you design for success by aligning with natural human behaviors: selfishness, fear and stupidity.